Resource information sharing in multi-domain optical grids. (1st January 2014) - Abouelela, Mohamed; El-Darieby, Mohamed
Providing interoperability in multi-domain optical grids requires sharing resource information among different domains. Sharing full resource information may not be appropriate due to security and business confidentiality reasons. We propose resource information sharing approach based on information aggregation and abstraction for both computing and networking resources. Information aggregation and abstraction affects the overall accuracy of information representation. This calls for more accurate information abstraction techniques. We propose three abstraction techniques: direct formulas, historical data and real-time measurements . The performance of the proposed information sharing approach and the abstraction techniques is evaluated by studying their impact on scheduling divisible load grid applications. Simulation results highlight the advantages of the proposed approach specially for data intensive applications. By using the proposed abstraction techniques, the same performance could be achieved as using large volumes of exact information.